Silver Nanowire Networks as Flexible, Transparent, Conducting Films: Extremely High DC to Optical Conductivity Ratios - COLEMAN, JONATHAN; BOLAND, JOHN; BLAU, WERNER (My University, 2009)
We have used aqueous dispersions of silver nanowires to prepare thin, flexible, transparent, conducting films. The nanowires are of length and diameter close to 6.5 ?m and 85 nm respectively. At low thickness, the films consist of networks but appear to become bulk-like for mean film thicknesses above ~160 nm. These films can be very transparent with optical transmittance reaching as high as 92% for low thickness. The transmittance (550 nm) decreases with increasing thickness, consistent with an optical conductivity of 6472 S/m. The films are also very uniform; the transmittance varies spatially by typically <2%. The sheet resistance decreases with increasing thickness, falling below 1 ?/ for thicknesses above 300 nm. The DC conductivity increases from 2'105 S/m for very thin films before saturating at 5'106 S/m for thicker films. Similarly, the ratio of DC to optical conductivity increases with increasing thickness from 25 for the thinnest films, saturating at ~500 for thicknesses above ~160 nm. We believe this is the highest conductivity ratio ever observed for nanostructured films and is matched only by doped metal oxide films. These nanowire films are electro-mechanically very robust, with all but the thinnest films showing no change in sheet resistance when flexed over >1000 cycles. Such results make these films ideal as replacements for indium tin oxide as transparent electrodes. We have prepared films with optical transmittance and sheet resistance of 85% and 13 ?/ respectively. This is very close to that displayed by commercially available indium tin oxide.
PUBLISHED
Keywords: conducting; Nanowires; electrode; flexible; transparent; Nanoscience & Materials